Preparation method and application of biochar composite ferroferric oxide photocatalyst

Through the preparation of biochar and iron tetraoxide composite photocatalyst, hydrothermal and calcining methods are used to decompose tetracycline in visible light, the problem of tetracycline pollution in the environment is solved and efficient and environmentally friendly degradation effect is achieved.

CN119236934AInactive Publication Date: 2025-01-03INNER MONGOLIA UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411152418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot effectively remove tetracycline pollution in the environment, and traditional methods are prone to lead to secondary pollution and high costs in the environment.

Method used

Biochar and iron tetraoxide were combined with iron tetraoxide, and photocatalysts were prepared by hydrothermal and calcining methods, and photogenetic electron-degraded tetracycline was captured under visible light.

Benefits of technology

The catalytic performance of the photocatalyst is improved, the recombination rate of photogenerated carriers is reduced, and the efficient tetracycline degradation is achieved. The raw materials are cheap, pollution-free, short preparation time and low energy consumption, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236934A_ABST
    Figure CN119236934A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a biochar composite ferroferric oxide photocatalyst, and relates to the technical field of photocatalyst preparation, and the preparation method specifically comprises the following steps: S1, preparing biochar; and S2, preparing the biochar composite ferroferric oxide photocatalyst. The photocatalyst disclosed by the invention is stable in performance, good in tetracycline degradation effect, high in light source utilization rate, low in raw material price, free of pollution, short in preparation time and low in energy consumption, and has a good application prospect in the fields of solving environmental pollution and energy crisis and photocatalysis application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst preparation, and in particular to a preparation method and application of a biochar composite ferroferric oxide photocatalyst. Background Art

[0002] With the continuous development of science and technology and medical level, the frequency of using tetracycline in pesticides and medicines is increasing. These natural activities of humans and animals have led to an increasing content of tetracycline in the ecological environment. Studies have shown that tetracycline and its intermediate molecules have been found in soil, groundwater and surface water in different regions. These tetracyclines not only damage the natural environment, but also enter the human and animal bodies with the enrichment of toxic substances, causing antibiotic resistance and seriously endangering the health of humans and animals. The removal of tetracycline in the environment is a global problem. The previous physical adsorption, chemical degradation and biological control methods are not ideal removal methods because they cannot be completely removed from the environment, are prone to secondary pollution to the environment and are easily affected by the environment.

[0003] Photocatalytic technology using semiconductors and their derivative materials as media can be used as a sustainable, pollution-free and efficient means to treat toxic substances such as wastewater and exhaust gas in the environment, thereby effectively solving the environmental problems facing mankind. According to literature reports, some researchers have successfully synthesized VP-Fe3O4 photocatalysts loaded with purple phosphorus Fe3O4 using a hydrothermal method using water as a solvent for the degradation of norfloxacin pollutants in water. However, this catalyst has problems such as the need to be used in conjunction with underwater bubble plasma (UBP) and the hydrothermal conditions are too high.

[0004] Based on this, developing a photocatalytic composite material that is easy to prepare and has excellent performance is a technical problem that people in this field urgently need to solve. Summary of the invention

[0005] In view of the above problems, the present invention provides a preparation method and application of a biochar composite ferroferric oxide photocatalyst.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing a biochar composite ferroferric oxide photocatalyst, which specifically comprises the following steps: S1: Preparation of biochar (BC): Grind the Radix Isatidis Chinese herbal medicine residue into powder and put it into a quartz boat, introduce N2 into a tube furnace, pyrolyze at a constant heating rate, cool to room temperature and grind to obtain biochar (BC); S2: Preparation of biochar composite ferroferric oxide (BC-Fe3O4) photocatalyst: Fe(NO3)3·9H2O was placed in a beaker, deionized water was added, and then the pyrolyzed biochar was added and stirred to obtain a mixed solution; the mixed solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for constant temperature reaction, and after the reaction was completed, it was cooled to room temperature, washed with deionized water and anhydrous ethanol for 3 times, dried, ground into powder, and placed in a quartz boat, and N2 was passed through a tubular furnace, calcined at a constant heating rate, and cooled to room temperature to obtain a biochar composite ferroferric oxide (BC-Fe3O4) photocatalyst.

[0007] Furthermore, in step S1, the heating rate is 10°C / min, the pyrolysis reaction temperature is 500°C, and the pyrolysis reaction time is 90min.

[0008] Furthermore, in step S2, the mass of Fe(NO3)3·9H2O is 0.31 g, 0.437 g, 0.576 g, 0.75 g or 0.94 g.

[0009] Furthermore, in step S2, the volume of the beaker is 100 mL, the volume of the deionized water is 20 mL, the mass of the biochar is 1 g, and the stirring time is 30 min.

[0010] Furthermore, in step S2, the volume of the polytetrafluoroethylene liner is 100 mL; the isothermal reaction temperature is 180° C., and the isothermal reaction time is 20 h; the drying temperature is 60° C.; the heating rate is 5° C. / min, the calcination reaction temperature is 600° C., and the calcination reaction time is 1 h.

[0011] The present invention also provides an application of a biochar composite ferroferric oxide photocatalyst, wherein the biochar composite ferroferric oxide photocatalyst degrades tetracycline under the conditions of visible light and sodium persulfate added to the reaction system.

[0012] Furthermore, the mass ratio of the biochar composite ferroferric oxide photocatalyst to tetracycline is 20:1.

[0013] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, the present invention uses the pyrolysis of Radix Isatidis Chinese medicinal material residue as biochar for the first time, and uses the hydrothermal and calcination methods to compound the biochar with ferroferric oxide, and uses the narrow band gap of ferroferric oxide and biochar as an electron transmission channel. The composite ferroferric oxide is used to activate persulfate to capture photogenerated electrons, and transmit them through biochar, which prolongs the life of photogenerated holes and photogenerated electrons, reduces the recombination rate of photogenerated carriers, and improves the catalytic performance of the photocatalyst. The photocatalyst prepared by the method of the present invention has stable performance, good tetracycline degradation effect, high light source utilization rate, low price and pollution-free raw materials, short preparation time, low energy consumption, good application prospects in solving environmental pollution, energy crisis and photocatalytic application fields, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a transmission electron microscope image of the 4-BC-Fe3O4 photocatalyst of the present invention; Figure 2 It is a diagram showing the effect of photocatalytic degradation of tetracycline by different catalysts of the present invention under visible light. DETAILED DESCRIPTION

[0015] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0017] Example 1 This embodiment provides a method for preparing a biochar composite ferroferric oxide photocatalyst, which specifically comprises the following steps: S1: Preparation of biochar (BC): Grind the Radix Isatidis Chinese herbal medicine residue into powder and put it into a quartz boat, introduce N2 into a tube furnace, pyrolyze at a heating rate of 10℃ / min, heat to 500℃ and keep for 90min, cool naturally to room temperature and grind to obtain biochar (BC); S2: Preparation of biochar composite ferroferric oxide (BC-Fe3O4) photocatalyst: 0.31g Fe(NO3)3·9H2O was placed in a 100mL beaker, 20mL deionized water was added, and 1g pyrolyzed biochar was added and stirred for 30min to obtain a mixed solution; the mixed solution was transferred to a hydrothermal reactor with a 100mL polytetrafluoroethylene liner and reacted at 180℃ for 20h. After the reaction was completed, it was cooled to room temperature, washed with deionized water and anhydrous ethanol for 3 times, dried at 60℃, ground into powder and placed in a quartz boat. N2 was passed through a tubular furnace, and the temperature was raised to 600℃ at a heating rate of 5℃ / min. It was calcined at a constant temperature for 1h and cooled to room temperature to obtain a BC-Fe3O4 composite material (15wt% BC-Fe3O4), that is, a biochar composite ferroferric oxide photocatalyst, recorded as 1-BC-Fe3O4.

[0018] The biochar composite ferroferric oxide photocatalyst is used for catalytic degradation of tetracycline under visible light, and the mass ratio of the photocatalyst to tetracycline is 20:1.

[0019] Example 2 The difference from Example 1 is that in step S2, the mass of Fe(NO3)3·9H2O is 0.437 g, and a BC-Fe3O4 photocatalyst (20 wt% BC-Fe3O4) is prepared, which is recorded as 2-BC-Fe3O4.

[0020] Example 3 The difference from Example 1 is that in step S2, the mass of Fe(NO3)3·9H2O is 0.576 g, and a BC-Fe3O4 photocatalyst (25 wt% BC-Fe3O4) is prepared, which is recorded as 3-BC-Fe3O4.

[0021] Example 4 The difference from Example 1 is that in step S2, the mass of Fe(NO3)3·9H2O is 0.75 g, and a BC-Fe3O4 photocatalyst (30 wt% BC-Fe3O4) is prepared, which is recorded as 4-BC-Fe3O4.

[0022] Example 5 The difference from Example 1 is that in step S2, the mass of Fe(NO3)3·9H2O is 0.94 g, and a BC-Fe3O4 photocatalyst (35 wt% BC-Fe3O4) is prepared, which is recorded as 5-BC-Fe3O4.

[0023] Comparative Example 1 The preparation method of pure BC photocatalyst is as follows: a certain mass of Radix Isatidis Chinese medicinal material residue is ground into powder and then put into a quartz boat, and pyrolyzed in a tubular furnace with N2 at a heating rate of 10°C / min. After heating to 500°C, it is maintained for 90 minutes and naturally cooled to room temperature to obtain the BC photocatalyst.

[0024] Comparative Example 2 The preparation method of pure Fe3O4 photocatalyst is as follows: 0.576g of commercially available Fe(NO3)3·9H2O is placed in a 100mL beaker, 20mL of deionized water is added to dissolve it, and then it is transferred to a hydrothermal reactor with a 100mL polytetrafluoroethylene liner, and a hydrothermal reaction is carried out at 180°C for 20h. After the reaction is completed, it is cooled to room temperature, washed, dried and ground, and then N2 is introduced into a tubular furnace for calcination to obtain Fe3O4 photocatalyst.

[0025] Experimental Example 1 Taking the 4-BC-Fe3O4 photocatalyst prepared in Example 4 as an example, the photocatalyst was tested by transmission electron microscopy. Figure 1 It can be seen that in the 4-BC-Fe3O4 photocatalyst, the Fe3O4 particles are distributed on the biochar without a crystalline structure, and the lattice spacing is 2.53Å and 2.96Å, corresponding to the (311) crystal plane and (220) crystal plane of Fe3O4, respectively, indicating the successful preparation of the BC-Fe3O4 photocatalyst.

[0026] Experimental Example 2 The photocatalysts prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-2 were used to degrade tetracycline solution under visible light conditions. The specific steps are as follows: take 15 mg of the photocatalyst sample, add it to 50 mL of 20 mg / L tetracycline solution (the mass ratio of tetracycline to photocatalyst is 1:20), ultrasonicate for 3 minutes, and add magnetons. Start the photocatalytic instrument, start the revolution, and start stirring. The reaction system was placed in the photocatalytic instrument and stirred for 10 minutes under dark conditions to facilitate the photocatalyst and the tetracycline solution to reach adsorption and decomposition equilibrium. 7-8 mL was sampled every 5 minutes, for a total of two times. After the sampling was completed, the circulating water was turned on, 25 mg of sodium persulfate (PDS) was added, and the xenon lamp light source was turned on to simulate visible light (Vis). Samples were taken once every 15 minutes for a total of 4 times, 7-8 mL each time. After the experiment, the light source was turned off, the photocatalytic instrument was turned off, and the circulating water was turned off. After filtering the sample solution, an ultraviolet spectrophotometer was used to detect the absorbance, as shown in Formula 1, and the results are attached. Figure 2 .

[0027] Formula 1 By the attached Figure 2It can be seen that the 1-BC-Fe3O4 photocatalyst of Example 1 can degrade 58% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The 2-BC-Fe3O4 photocatalyst of Example 2 can degrade 74.1% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The 3-BC-Fe3O4 photocatalyst of Example 3 can degrade 78% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The 4-BC-Fe3O4 photocatalyst of Example 4 can degrade 87% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The 5-BC-Fe3O4 photocatalyst of Example 5 can degrade 85% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The pure BC photocatalyst of Comparative Example 1 can degrade 42.6% of a 20 mg / L tetracycline solution in 60 minutes under visible light irradiation. The pure Fe3O4 photocatalyst of Comparative Example 2 can degrade 51.3% of a 20 mg / L tetracycline solution in 60 min under visible light irradiation. It can be seen that the biochar composite ferroferric oxide photocatalyst prepared in Examples 1-5 has a good degradation effect on tetracycline.

[0028] The biochar composite ferroferric oxide photocatalyst used in this embodiment generates photogenerated electron-hole pairs from the ferroferric oxide excited by light. The biochar, as an electron transmission channel, can accelerate the transfer of photogenerated charges, increase the lifespan of photogenerated electrons and holes, reduce the recombination rate of photogenerated carriers, and improve its photocatalytic activity. At the same time, the photogenerated electrons can activate persulfate to generate sulfate radicals (SO4 ·- ) to degrade tetracycline antibiotics.

[0029] In summary, the photocatalyst composite material prepared in this embodiment has stable performance, good degradation effect on tetracycline, the raw materials used are inexpensive and pollution-free, the preparation time is short, and the energy consumption is low. It has good application prospects in solving environmental pollution, energy crisis and photocatalytic application fields, and can be mass-produced.

[0030] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biochar composite ferroferric oxide photocatalyst, characterized in that: The specific steps include: S1: Preparation of biochar: Grind the Radix Isatidis Chinese medicinal material residue into powder and put it into a quartz boat, introduce N2 into a tube furnace, pyrolyze at a constant heating rate, cool to room temperature and grind to obtain biochar; S2: Preparation of biochar composite ferroferric oxide photocatalyst: Place Fe(NO3)3·9H2O in a beaker, add deionized water, then add pyrolyzed biochar and stir to obtain a mixed solution; transfer the mixed solution to a hydrothermal reactor with a polytetrafluoroethylene liner for constant temperature reaction, cool to room temperature after the reaction is completed, wash with deionized water and anhydrous ethanol 3 times, dry, grind into powder and put into a quartz boat, pass N2 in a tubular furnace, calcine at a constant heating rate, and cool to room temperature to obtain a biochar composite ferroferric oxide photocatalyst.

2. The method for preparing a biochar composite ferroferric oxide photocatalyst according to claim 1, characterized in that: In the step S1, the heating rate is 10°C / min, the pyrolysis reaction temperature is 500°C, and the pyrolysis reaction time is 90min.

3. The method for preparing a biochar composite ferroferric oxide photocatalyst according to claim 1, characterized in that: In step S2, the mass of Fe(NO3)3·9H2O is 0.31 g, 0.437 g, 0.576 g, 0.75 g or 0.94 g.

4. The method for preparing a biochar composite ferroferric oxide photocatalyst according to claim 1, characterized in that: In step S2, the volume of the beaker is 100 mL, the volume of deionized water is 20 mL, the mass of the biochar is 1 g, and the stirring time is 30 min.

5. The method for preparing a biochar composite ferroferric oxide photocatalyst according to claim 1, characterized in that: In the step S2, the volume of the polytetrafluoroethylene liner is 100 mL; the isothermal reaction temperature is 180° C., and the isothermal reaction time is 20 h; the drying temperature is 60° C.; the heating rate is 5° C. / min, the calcination reaction temperature is 600° C., and the calcination reaction time is 1 h.

6. Use of the biochar composite ferroferric oxide photocatalyst prepared by the method for preparing a biochar composite ferroferric oxide photocatalyst according to any one of claims 1 to 5, characterized in that: The biochar composite ferroferric oxide photocatalyst degrades tetracycline under the conditions of visible light and sodium persulfate added into the reaction system.

7. The use of the biochar composite ferroferric oxide photocatalyst prepared by the method for preparing a biochar composite ferroferric oxide photocatalyst according to claim 6, characterized in that: The mass ratio of the biochar composite ferroferric oxide photocatalyst to tetracycline is 20:1.

Citation Information

Cited By

  • Preparation method of carbon-coated Fe3O4 (at) C catalyst and application of carbon-coated Fe3O4 (at) C catalyst in degradation of antibiotics

    CN120325279A